2015
DOI: 10.1111/jbg.12171
|View full text |Cite
|
Sign up to set email alerts
|

Two single nucleotide polymorphisms in the promoter of the ovine myostatin gene (MSTN) and their effect on growth and carcass muscle traits in New Zealand Romney sheep

Abstract: Myostatin is a negative regulator of muscle growth and development in mammals, and variation in ovine myostatin gene (MSTN) has been demonstrated to be associated with variation in the muscularity of sheep. Polymerase chain reaction-single-stranded conformational polymorphism (PCR-SSCP) was used to look for single nucleotide polymorphisms (SNPs) in a 304-bp amplicon from the promoter region of ovine MSTN. Sequence analyses revealed two previously identified SNPs (c.-2449G/C and c. -2379T/C) that resulted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…Moreover, conversely to our results Crispo et al [41] and Li et al [42] showed significant differences between the WT and the MSTN KO lambs in postnatal growth and development. Results of Crispo et al [41] are with disagreement not only with our present studies, but also with outcomes of other authors, e.g., [10,16,34], who have observed the effects of polymorphisms in the MSTN gene on birth weight. Conversely, several authors, e.g., [15,38], did not observe effects of the MSTN gene polymorphisms on postnatal growth.…”
Section: Effects Of Mstn Alleles and Genotypes On Growth Traitscontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, conversely to our results Crispo et al [41] and Li et al [42] showed significant differences between the WT and the MSTN KO lambs in postnatal growth and development. Results of Crispo et al [41] are with disagreement not only with our present studies, but also with outcomes of other authors, e.g., [10,16,34], who have observed the effects of polymorphisms in the MSTN gene on birth weight. Conversely, several authors, e.g., [15,38], did not observe effects of the MSTN gene polymorphisms on postnatal growth.…”
Section: Effects Of Mstn Alleles and Genotypes On Growth Traitscontrasting
confidence: 99%
“…Moreover, the c.*1232G>A substitution was associated with lamb live weight in 8 weeks of age in Texel x Welsh Mountain lambs [36]. Interestingly, Wang et al [16] found association between the nucleotide variation in a promoter region of the MSTN gene (c.-2379) and birth, tailing and weaning weights. Moreover, Han et al [37] investigated SNPs in the promoter, the first exon and intron, as well as the 3 UTR region of the MSTN gene and they observed highly significant (p = 0.006) and significant (p = 0.02) effects of the H1 haplotype on tailing weigh (approximately 3 weeks after birth) and growth rate to weaning, respectively.…”
Section: Effects Of Mstn Alleles and Genotypes On Growth Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…In NZ Romney, two additional SNPs—c.–2449G/C and c.–2379T/C—were detected (Wang et al . ). The c.*123A variant observed in NZ cross‐bred sheep was also reported in Texel (Kijas et al .…”
Section: Double Muscling In Sheepmentioning
confidence: 97%